Does the Size of a Company Make a Difference in the Prevalence of Exposure to Asthmagens and in the Use of Respiratory Protective Equipment? - El-Zaemey, Sonia; Carey, R.; Darcey, E.; Reid, A.; Rushton, L.; McElvenny, D.; Fritschi, Lin (2018)
Introduction: About half of all workers in high-income countries work in small companies. However, regulatory bodies and researchers predominantly work with large companies because they are more convenient to study and easier to reach. We aimed to estimate the prevalence of exposure to asthmagens and the use of respiratory protective equipment (RPE) by company size. Methods: This analysis used data from the Australian Work Exposures Study-Asthma, a telephone survey which investigated exposure to 27 asthmagen groups. Results: Among 4844 respondents, 18.8, 19.9, 31.9, and 29.4% of workers reported working in micro (<5 employees), small (5-19 employees), medium (20-200 employees), and large (>200 employees) companies, respectively. Compared to workers in large companies, workers in micro, small, or medium companies had higher prevalence of exposure to most asthmagens and lesser use of RPE. Conclusion: Our results suggest that policy actions and regulatory measures should target micro/small companies in order to have the greatest effect.